Penyuluhan Pembuatan Pupuk Organik Cair Eceng Gondok dan Keong Mas sebagai Upaya Pemberdayaan bagi Ibu PKK di Desa Tlompakan Kabupaten Semarang - Muhimmatul Ifadah; Rafaella C. Megananda; Nabilatus Sunayya; Afni Harfina; Florentina Kusmiyati (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2021)
The purpose of this community service activity is to increase the insight of PKK Dusun Semen on the process of processing liquid organic fertilizer from water hyacinth and golden snail. Water hyacinth and golden snail are used as basic ingredients for making liquid organic fertilizer because they are abundant and have potential as liquid organic fertilizer. Extension activities were carried out using the lecture method and Focussed Group Discussion (FGD). Based on the counseling activities that have been carried out, Ms. PKK has begun to understand the stages of the process of making liquid organic fertilizer from water hyacinth and golden snail. The support from the head of the PKK and the enthusiasm of Mrs. PKK were seen during the extension activities.